Analysis of Governance & Performances of Mergers and Acquisitions: Impact of Good Governance on Post M&A Financial Performance (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In the present paper,we construct a corporate governance index for a sample of 93 Indian companieslisted on Bombay Stock Exchange and National Stock Exchange. The index is basedon a comprehensive set of 64 governance attributes for these sample companies,the companies, then, have been classified into four governance portfolios usingtheir corporate governance ranking. Furthermore, we have calculated average of3 years post - mergers and acquisitions (M&A) financial performance andvaluation ratios for each governance portfolio. Our findings suggest goodgovernance appears to be of much value as we found significant higher postmergers and acquisitions rate of return ratios for companies in top quartiles.We also report significant higher valuation ratios for companies in topgovernance portfolio. The  present  study concludes that  companies  with higher  rank  for corporate  governance  score are  good  performers which  are  revealed from  better  financial ratios.  Their post M&A better financialperformance and valuation shows that good governed companies bring positivesynergies from their M& A activities which is recognized by marketreflected in higher valuation ratios.